„Narrowcasting” w miejscach użytecznooeci publicznej - Piesiewicz, Piotr F. (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
The present forms of communication, whether via picture or sound, assume various forms. Every new form of such communication poses a new challenge, not only for technicians and computer scientists, who analyze issues regarding the direct servicing of such messages on a continuous basis, but also for lawyers. Narrowcasting is among the new forms of transmitting audiovisual messages. This phenomenon was mentioned in the doctrine of J. Barta and R. Markiewicz. T. Goban-Klas and P. Sienkiewicz were right when they observed that the new ways of delivering information take the form of a so-called narrowcasting, i.e. communication which is only targeted at selected recipients and involves segmentation of the audience. The authors stressed the difference which occurs between a speech delivered to numerous listeners and impersonal mass communication (the difference is erased by applying the single notion of allocution). The new medium has provided an opportunity to overcome the quasi-monopoly of the mass media in the field of indirect social communication. On the other hand, the higher level of addressability of the new media (i.e. narrowcasting as opposed to broadcasting, or collectiveness as opposed to dispersion) poses new dilemmas for the communicators.